Training the Human Animal: Biopolitics and Anthropotechnics - Carlos Ernesto Noguera-Ramírez; Dora Lilia Marín-Díaz (Universidade de Lisboa, 2016)
This article presents a reflection about the training process, the culture of the human animal. Based on analyses by Nietzsche, Foucault and Sloterdijk, we argue that the recognition of humans as a technical animal was the basis for modern government art. It analyzes the demographic policy of the dawn of modernity that was one of the first biopolitical operations, the result being the overproduction of biological humans and the subsequent emergence of a set of disciplinary anthropotechnics for its government. The unforeseen surplus of this technique operation was the essential requirement for the configuration of the rationality of liberal government with its liberal anthropotechnics and with them the mass production of sovereign human beings: mobile and flexible identities that self-produce, through the Operation of techniques that can choose according to their own needs and desires.